KIKS Creativity and Technology for All - Houghton Tony; Oldknow Adrian; Diego-Mantecón José Manuel; Fenyvesi Kristof; Crilly Elizabeth; Lavicza Zsolt (De Gruyter, 2019)
To help meet an educational and societal requirement for all students to enjoy, have confidence and ability in creativity and technology, the "Kids Inspiring Kids in STEAM" (KIKS) EU project adopted an intensive Hothousing process challenging students in Finland, Spain, Hungary and the United Kingdom to engage in collaborative problem solving to develop solutions to: "How would you get your schoolmates to LOVE STEAM?" The project provided a process and technology toolkit for students, including those with special educational needs, to achieve their solutions.